TANGGUNG GUGAT PERDATA BANK TERHADAP KLAIM BANK GARANSI YANG DIKELUARKAN - Pramono, Youngky Yudho (Jurnal Cakrawala Hukum, 2017)
Stable economic growth, accompanied by equitable development and the level of public confidence in the government over the development of infrastructure it works, not only the government alone the private sector also participate play a role in building the country. This writing has the purpose of knowing how the Bank’s Liability Against Bank Guarantee Claims if the guaranteed party (contractor) performs a default, to identify and analyze the constraints faced by the guarantor (bank) to sue and collect the assured (contractor) after obtaining Bank Guarantee claims from the recipient of the guarantee (employer). This type of research uses a kind of juridical-empirical research which means this study describes the facts that occur in the field and know the effectiveness of the validity of positive law in society. Empirical research is a research on the implementation of a rule of law, especially the Law related to Bank Guarantee. This writing focuses on the issue of civil liability of banks against bank guarantee claims, if the guaranteed party (contractor/contractor) to do wanprestasi. Barriers facing banks to sue and collect are secured after obtaining bank guarantee claims.DOI: https://doi.org/10.26905/idjch.v8i2.1672